Inheritance Rights of Orphaned Grandchildren under Section 4 of Muslim Family Law Ordinance, 1961 and its Alternative Solutions - Fatima, Haseeb (Law and Policy Review, 2024)
Islamic law of inheritance has extensively explained the entitlement and shares of different legal heirs in the estate of the deceased person. The shares of heirs are fixed and Allah Almighty knows its wisdom. Humans cannot meticulously comprehend its logic. For inheriting the share in the estate of propositus, the heir must be in nearer degree to the deceased person and must be alive at the time of the opening of the succession. However, heirs who are in distant relation to the deceased and also who are not alive upon the demise of the deceased are excluded from inheritance. In the classical law of inheritance, children of predeceased son/daughter (i.e., grandchildren) do not inherit any share from the estate of propositus if the direct children (sons or daughters) of the deceased are still alive. Therefore, for the protection of the inheritance rights of orphaned grandchildren, Section 4 of the Muslim Family Laws Ordinance 1961(hereinafter MFLO) was enacted. Section 4 grants a share to orphaned grandchildren under the principle of representational succession. This provision of law deviates from the traditional scheme of inheritance. Finally, in the case of Allah Rakha v. Federation of Pakistan (2000), the Federal Shariat Court declared it an un-Islamic provision of law. This article explores the place of orphaned grandchildren in the classical Islamic law of inheritance. It also examines the representational succession under Section 4 along with its different alternatives. This article concludes that Section 4 is a controvertible provision and its judicial construction is also multiplicate. Therefore, it is the responsibility of the state to devise welfare schemes for redressing the economic grievances of orphaned grandchildren.